PENGARUH METODE KOOPERATIF TEKNIK NHT TERHADAP HASIL BELAJAR DAN RESPON SISWA PADA MATERI KONSEP MOL - Sarpianto, Sarpianto; Enawaty, Eny; Sarti, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine whether there is a difference between the learning outcomes of students who are given cooperative learning techniques Numbered Heads Together (NHT) with students given conventional learning on mole concept materials, the influence of cooperative learning techniques NHT in improving learning outcomes and student responses to learning cooperative NHT technique on mole concept material. The form of research used is quasi experimental design with "Nonequivalen Control Group Design" research design. Sampling using purposive sampling technique, and selected student class XC as expriment class while XA as control class. Data collection tool used in this study is the test of learning outcome and student response questionnaire. Hypothesis test results using T test with Î± of 5%, t count> ttable is 8.06> 1.68. This means that there is a difference between the learning outcomes of the control class students who were taught using conventional methods with the expression classes that were taught using the cooperative model of NHT model. Calculation of Effect Size value of 1.4 shows that cooperative learning techniques NHT gives 41.92% influence in improving student learning outcomes class X SMA 2 Mandor. Student response to cooperative learning technique NHT gave positive response with approval level of 85,04%.Â Keywords: Co-operative, NHT, learning outcomes, response